Influences and Outcomes: A Systematised Review of Reflective Teaching Strategies in Student Healthcare Placements - Dunne, Michael; Nisbet, Gillian; Penman, Merrolee; McAllister, Lindy (International Journal of Practice-based Learning in Health and Social Care, 2016)
The development of reflection in tertiary students benefits from facilitation. Educators commonly facilitate the development of affective, cognitive, and meta-cognitive skills associated with reflection. Reflective teaching strategies, that is, guiding comments or questions used within an activity to stimulate cognitive processes, are strategies used by educators to facilitate reflection. This systematised review focuses on the approaches used to measure influences and outcomes of the teaching of reflection in order to enhance educators’ understanding of recent evidence for use in the placement setting. The review explores what outcome measures are used in current research, and how the evidence incorporates contextual factors such as time, safety, mentorship, supervision, and emotional and intellectual support to develop reflection in students. Systematised searching of CINAHL®, ProQuest, ERIC, OvidSP, Scopus®, and Web of Science™ databases for the period 2005 to 2015 identified 26 studies, from a pool of 6968 that met the inclusion criteria. Results indicate that a range of reflective teaching strategies are being used by allied and oral health, nursing, and the medical professions that assist movement towards critical reflection. No direct connection between this movement and the presence of contextual factors was established. Review outcomes are limited by the variable quality of the included studies and the lack of high quality tools for measurement of teaching effect on the development of reflection. We recommend that future studies into the use of reflective teaching strategies continue to incorporate contextual factors in combination with valid and reliable measurement practices in the workplace.